(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe epidermiology, clinical and sub-clinical characteristics of patients with scabies. Subjects and methods: A cross-sectional descriptive study of 126 patients diagnosed with scabies via clinical examination and detection of scabies through KOH examination or dermscopy examination at the NHDV from August 2017 to July 2018. Results: 93/126 patients (73.8%) were males and 33/126 patients (26.2%) were females. Children and students were the two groups with the highest proportion of contrating the disease (33.5% and 26.2%, respectively). The proportion of patients knowing the source of infection was 64.3%. Sixty six point seven percent of patients had homemates or family members having symptoms of scabies. Patients from rural areas accounted for 57.1% while patients from urban areas accounted for 42.9%. The most common locations of scabies lesions were fingers, palms (90.5%), and feet, toes (76.2%). The rate of detecting scabies parasites by KOH examination was 5/85 (5.9%), while this rate by dermoscopy was 77/85 (90.6%), the difference was statistically significant with p <0.001. Conclusion: Scabies tended to affect more men than women and were observed more common in children and students. The incidence of scabies in rural and urban areas was not much different in our study. Dermoscopy was a simple, convenient test to detect scabies parasites with a detection rate of scabies parasites 15.3 times higher than KOH examination.